PENGEMBANGAN INSTRUMEN PENILAIAN BENTUK MULTIPLE CHOICE BERBASIS HOTS PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 1 UJUNG BATU ROKAN HULU - Afini Nurul Hidayat; Miftahurrizqa, Miftahurrizqa; Risnawati, Risnawati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to develop an assessment instrument in the form of multiple choice based on Higher Order Thinking Skills (HOTS) in Islamic Religious Education (PAI) subjects at SMPN 1 Ujung Batu, Rokan Hulu. The assessment instruments developed are expected to measure students' high-level thinking skills, which include analysis, evaluation, and creation skills. The research method used is Research and Development (R&D) with the Borg and Gall development model which consists of ten steps, but in this study, it is simplified into seven main steps: (1) initial research and information collection, (2) planning, (3) initial product development, (4) initial field trials, (5) product revision, (6) main field trials, and (7) final product refinement. The subject of this study is grading VII A students at SMPN 1 Ujung Batu which totals 30 students. Data was collected through questionnaires and tests that were analyzed in a quantitative and qualitative descriptive manner. The results of the study show that the HOTS-based multiple choice assessment instrument developed is valid and reliable to be used in assessing students' high-level thinking skills in PAI subjects. This instrument has been proven to be able to improve students' critical thinking skills, as well as provide challenges that are appropriate to their level of cognitive development. Feedback from teachers and students also shows that this instrument can motivate students to learn more deeply and critically in understanding PAI material.